2022
DOI: 10.1108/pijpsm-03-2022-0041
|View full text |Cite
|
Sign up to set email alerts
|

A study on the mediating effects of anxiety and happiness for workplace loneliness and behavioral outcomes of Korean police officers

Abstract: PurposeWorkplace loneliness has become a concern in diverse work settings. However, workplace loneliness research is in its early stages of development and not much is known about the effects of it on organizations and its members, especially in police organizations. The purpose of this study is to investigate the relationships between workplace loneliness, anxiety, happiness, task performance, and organizational citizenship behavior (OCB). Data from police officers in Korea were used to test these relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…Researchers discovered that anxiety is connected with Counterproductive Work Behavior in general (Fox and Spector, 1999;Fox et al, 2001). Chung et al (2022) found evidence of anxiety mediating work behavior especially OCB and Wang et al (2021) found evidence for leader workplace anxiety to be associated with employee OCB.…”
Section: Anxietymentioning
confidence: 99%
“…Researchers discovered that anxiety is connected with Counterproductive Work Behavior in general (Fox and Spector, 1999;Fox et al, 2001). Chung et al (2022) found evidence of anxiety mediating work behavior especially OCB and Wang et al (2021) found evidence for leader workplace anxiety to be associated with employee OCB.…”
Section: Anxietymentioning
confidence: 99%
“…Digital shared services make work constantly "invade" employees' lives, creating "technology invades life" stress [7][8]. Some studies have found that individual stress is related to negative emotions, and when individuals feel stress, it can cause negative emotions such as anxiety, depression, and anxiety [9].…”
Section: Introductionmentioning
confidence: 99%